TAREKAT KHALWATIYAH DI MESIR DAN BANJA; DIALEKTIKA SPIRITUALITAS DAN TRANSFORMASI SOSIAL DALAM ARUS MODERNITAS - Izhar Muttakin (As-Sulthan Journal of Education, 2026)
This article examines the dialectic between spirituality and social transformation in the practice of the Khalwatiyah Order in two different cultural contexts beetwen Egypt and Banjar (South Kalimantan). By combining a social Sufism approach and social transformation theory, this study shows how the order acts as a spiritual and social force that is adaptive to the currents of modernity. In Egypt, the Khalwatiyah Order grew within the framework of urban Sufism integrated with the Al-Azhar scientific institution, demonstrating the order's ability to respond to modernity by emphasizing Qur'anic rationality and morality. Meanwhile, in Banjar, the teachings of Khalwatiyah are manifested through the Sammaniyah Order, which is deeply rooted in local traditions and the charismatic authority of the ulama, particularly through the figure of K.H. Muhammad Zaini Ghani (Guru Sekumpul). This study finds that both contexts show different patterns of spiritual adaptation but both affirm the role of the order as an agent of social transformation and a bridge for Islamic transnationalism. Thus, the order functions not only as a space for spiritual guidance but also as an arena for the negotiation of values, identity, and cultural resistance to the challenges of global modernity.